Optimization of Desulfurization of 4-Methyldibenzothiophene and 4,6-Dimethyldibenzothiophene Using Mg/Al Layered Double Hydroxide Equipped with ZnO/TiO2 - Amri, Amri; Ahmad, Nur; Wibiyan, Sahrul; Wijaya, Alfan; Mardiyanto, Mardiyanto; Royani, Idha; Mohadi, Risfidian; Lesbani, Aldes (Indonesian Journal of Chemistry, 2024)
The growth of heavy industry leads to an increase in sulfur dioxide emissions, impacting health, economy, and the fulfilment of the ecological needs for society. Sulfur removal is carried out using the oxidative desulfurization (ODS) method. In this study, layered double hydroxide materials of Mg/Al, Mg/Al-TiO2, and Mg/Al-ZnO were successfully synthesized and analyzed using X-ray diffraction (XRD), Fourier-transform infrared (FTIR), and scanning electron microscope-energy dispersive spectroscopy (SEM-EDS) techniques. Those materials are used as catalysts for the desulfurization of 4-methyldibenzothiophene (4-MDBT) and 4,6-dimethyldibenzothiophene (4,6-DMDBT). Composite Mg/Al catalysts with metal oxides provide superior desulfurization process efficiency and enhanced stability, making them highly effective for repeated use. The conversion percentage of desulfurization of 4-MDBT and 4,6-DMDBT increases with time. The n-hexane is a suitable solvent for desulfurization of 4-MDBT and 4,6-DMDBT. All catalysts exhibit significant heterogeneity that greatly aids in the separation process.